Gain Enhancement of E-Shaped Microstrip Patch Antenna for Underground RFID Reader Application - Mohamad Fadhil, Nurul Husna; Karim, Jamilah; Abd Rahman, Nurul Huda; Subahir, Suhaila; Chan, Kean Mun; Zainol Murad, Sohiful Anuar (International Journal of Integrated Engineering, 2025)
Radio Frequency Identification or (RFID) is a wireless communication technology that uses radio waves and consists of a reader, tag, and antenna. This paper introduces an innovative concept: an E-shaped microstrip patch antenna utilizing an air gap substrate. The proposed design is tailored for the specific application of underground RFID readers, aiming to optimize the antenna’s performance within this unique context. The study encompassed the execution of a parameter analysis to thoroughly explore and optimize the impact of alterations in the antenna dimension on the performance of S11. The antenna design uses coaxial probe feeding technique with aluminum patch. Then, the performance of the final antenna design is analyzed and evaluated. The gain obtained for the proposed design is 9.121 dBi, while the S11 value at the desired resonant frequency 921 MHz is -11.99 dB. The simulation is performed with CST suite software.